2021
DOI: 10.1002/mmce.22575
|View full text |Cite
|
Sign up to set email alerts
|

Gain augmentation of a dual‐band dielectric resonator antenna with frequency selective surface superstrate

Abstract: Gain augmentation of a dual‐band antenna with different bandwidths using superstrate is presented in this paper. Initially, the dual‐band radiator is designed using a rectangular dielectric resonator (DR). The fundamental mode TE111 of the rectangular DR resonates at 3 GHz over a narrowband (BW = 5.08%). The upper wideband (BW = 20% with center frequency 5.86 GHz) is obtained by the amalgamation of two hybrid modes with higher‐order TE113 mode. The dielectric waveguide model is used for the theoretical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The technique of superstrate loading has been widely used to improve the gain of patch antennas, 9,10 dielectric resonator antennas, 11–14 and directional slot antennas 15–19 . Superstrate loaded antennas, also known as the resonant cavity antennas produce high gain through multiple reflections between itself and the ground plane through the Fabry‐Perot cavity effect 17,20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique of superstrate loading has been widely used to improve the gain of patch antennas, 9,10 dielectric resonator antennas, 11–14 and directional slot antennas 15–19 . Superstrate loaded antennas, also known as the resonant cavity antennas produce high gain through multiple reflections between itself and the ground plane through the Fabry‐Perot cavity effect 17,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The wider bandwidth feature of slot antennas has given rise to several wideband and ultra-wideband antenna designs using simple techniques such as offset fed slot, 2,4,5 wide slot fed with fork-like microstrip, 5-7 and stub loaded slot. 8 The technique of superstrate loading has been widely used to improve the gain of patch antennas, 9,10 dielectric resonator antennas, [11][12][13][14] and directional slot antennas. [15][16][17][18][19] Superstrate loaded antennas, also known as the resonant cavity antennas produce high gain through multiple reflections between itself and the ground plane through the Fabry-Perot cavity effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method is not suitable for all applications due to the limitation of the compact installation platform. Therefore to solve these issues, varieties of gain enhancement techniques, such as the use of electromagnetic bandgap (EBG) structure [17], metallic cap [18], different feeding mechanisms [19], stacked configured of different layers [20], frequency selective surfaces (FSS) [21], and superstrate layer [22][23][24][25][26], are developed by researchers. In most of the reported articles, it is observed that the gain enhancement at the lower frequencies by maintaining the miniaturized dimension becomes a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many researchers are interested in Dielectric Resonator Antennas (DRAs). This theme was introduced in 1983 [1], and they have been widely studied and used owing to their attractive properties like small size, low ohmic loss, light weight, ease of excitation, wide bandwidth, and very high radiation efficiency in compared with planner antenna [2][3][4][5][6]. They are used in both linearly and circularly polarized systems [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%